Ventral Tegmental Area Afferents and Drug-Dependent Behaviors - Oliva, Idaira; Wanat, Matthew J. (Frontiers in Psychiatry, 2016)
Drug-related behaviors in both humans and rodents are commonly thought to arise from aberrant learning processes. Preclinical studies demonstrate that the acquisition and expression of many drug-dependent behaviors involves the ventral tegmental area (VTA), a midbrain structure comprised of dopamine, GABA and glutamate neurons. Drug experience alters the excitatory and inhibitory synaptic input onto VTA dopamine neurons, suggesting a critical role for VTA afferents in mediating the effects of drugs. In this review we present evidence implicating the VTA in drug-related behaviors, highlight the diversity of neuronal populations in the VTA, and discuss the behavioral effects of selectively manipulating VTA afferents. Future experiments are needed to determine which VTA afferents and what neuronal populations in the VTA mediate specific drug-dependent behaviors. Further studies are also necessary for identifying the afferent-specific synaptic alterations onto dopamine and non-dopamine neurons in the VTA following drug administration. The identification of neural circuits and adaptations involved with drug-dependent behaviors can highlight potential neural targets for pharmacological and deep brain stimulation interventions to treat substance abuse disorders.